direct and indirect impacts of marine acidification on the ecosystem services provided by coralligenous reefs and seagrass systems - Zunino, Serena; Canu, Donata Melaku; Zupo, Valerio; Solidoro, Cosimo (Global Ecology and Conservation, 2019)
Increasing emissions of CO2 and the resultant ocean acidification (OA) will have large implications for the marine ecosystems sustained by habitat-forming species and their related ecosystem services (ES), with potentially significant impacts on human well-being. Here, we provide an assessment of the direct and indirect impacts of OA on ES. The changes in the functioning of coralligenous reefs and Posidonia oceanica meadows promoted by OA were investigated by i) synthesizing current knowledge into conceptual models. The models were then used to, ii) assessing the impacts of exposure of the selected taxa at the acidification level associated with two CO2 emission scenarios and iii) using the conceptual model outputs to project the cascading impacts from individuals to functions to ES.The results highlight that the combination of the direct and indirect effects of acidification will alter many functions of both coralligenous and P.oceanica systems, triggering habitat modifications and the loss of highly valuable ES.While the exact timing of the expected changes will depend on the severity of the emission scenarios, significant and hardly reversible changes can be expected as quickly as a few decades under the business-as-usual scenario, and many ecosystem services are at risk even under much more conservative scenarios. Keywords: Ocean acidification, Posidonia oceanica, Coralligenous, Ecosystem services, Mediterranean sea, Conceptual models